The Effect of Institutional Ownership, Families’ Ownership, Ownership Concentration and Dividend Policy Towards Firm Performance - Teguh Ade Putra; Andreas Andreas; Enni Savitri (Indonesian Journal of Economics, Social, and Humanities, 2022)
This purposed of this study is to analyze the effect of institutional ownership, family’s ownership, ownership concentration and dividend policy towards firm performance. This type of quantitative research, the data used secondary data. The population in this research were the manufacture companies listed in Indonesia Stock Exchange (BEI) during period 2015 until 2017. Sample selection method was using with technique purposive sampling, with certain proposals selected by 90 companies. Data collection methods in this research are literature study and internet access. The data was analysed by multiple linear regression. The results showed that institutional ownership has impact toward firm performance, family’s ownership does not impact toward firm performance, ownership concertation has impact toward firm performance and dividend policy has impact toward firm performance.